Envelhecer no lugar: A garantia de direitos dos Idosos junto a Defensoria Pública da Comarca de São Carlos - Santos, Luiz Eduardo dos (Universidade Federal de São Carlos, 2021)
The present study aimed to analyze the profile of the demand of the Public Defender of the County of São Carlos-SP, in the defense of the rights of the older people through The present study aimed to analyze the profile of the demand of the Public Defender of the County of São Carlos-SP, in the defense of the rights of the older people through the survey of lawsuits, during the period from January to October 2017. We used the quantitative and qualitative method of analyzing the allegations present in the proceedings initiated. It was verified that the binomial urgency and necessity, imposed on the elderly individual the judicial sphere as the only possible for the satisfaction of their demands, which are related to issues of: health, family and burdensome demands. The increase in life expectancy, as a contemporary socio-demographic phenomenon, establishes a new profile of the elderly in our society, which in view of their specificity needs to be better served by the public authorities. It is concluded that, by improving public policies on access to medicines and social support for vulnerable families, the elderly may have a better quality of life.
Aging in place: The guarantee of the rights of the older people with the Public Defender of the District of São Carlos
Keywords: Idoso; Política pública; Defensoria pública; Qualidade de Vida; Justiça social; Older people; Public policy; Public Defender; Quality of Life; Social Justice; OUTROS